Radical Islamic Terrorism in the Middle East and Its Direct Costs on Western Financial Markets - Martin Mullins; John Garvey (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Close examination of the behaviour of participants in financial markets in the aftermath of terrorist attacks is a valuable line of enquiry. In this paper, we bring together insights from field of finance and politics. Specifically, we examine trading patterns on highly liquid insurance-type financial instruments around a specific terrorist event. This approach provides an insight into risk perception around political violence and allows us to answer a number of key questions on the impact of terrorist attacks on economies and societies. When examined and processed, intraday financial trade data yields valuable empirical evidence on immediate reactions to the threat posed by terrorist groups. The methodology applied in this paper also tells us much about the geographical resonance of terrorist events. We clearly show that fear of economic disruption can be activated in Western markets by events that are often geographically remote. Importantly, these datasets allow us to judge the vulnerability of financial markets to terrorist attack. This potentially allows public authorities to safeguard our interests more effectively. Financial markets are one important element of a "neglected home front" and the risks posed by disruption to those markets are such as to merit our urgent attention.
Keywords: 330